Social and Science Students’ Perception on the Use of Google Form as an Online Assessment - Chikmah, Faik Qotul; Lestari, Erma Rahayu (ICONELT, 2022)
The purpose of this study was to determine the perceptions of social and science students on the use of Google Form as an online assessment in Senior High School Ploso. The method used in this research is quantitative method which using survey design from cross-sectional survey to 120 eleventh and twelfth grade students of SMAN Ploso, of which 60 social students and 60 science students. Close-ended questionnaire was used as an instrument in this study. The results show that social and science students have mean scores that fall into the medium and high categories. These two categories can be indicated into the category of positive perceptions. So the conclusion is social and science students have positive perceptions of using Google Form as an online assessment in Senior High School Ploso.